Good Sleep = Good Health (Homoeopathy for All, 2024)
Early to bed & early to rise, makes a  man healthy, wealthy & wise. Since  ages good health & wealth have  been associated with a good night’s  sleep. Sleep is the rest our body  & mind need on a daily basis to  function well. It is equally important  to prioritise sleep as it is to exercise  or work.
Keywords: healthy; function; wealthy